2002
DOI: 10.1038/sj.bmt.1703703
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of toxigenic Clostridium difficile infections after hematopoietic stem cell transplantation: implications for symptomatic management of diarrhea

Abstract: Summary:Diarrhea is a common complication of high-dose chemotherapy and hematopoietic stem cell transplantation (HSCT). The frequent and prolonged use of multiple antibiotics in this setting can predispose to infection with toxigenic Clostridium difficile and the development of pseudomembranous colitis. Anti-motility agents are usually not administered in this setting until C. difficile infection has been excluded. The objective of this study was to determine the incidence of C. difficile toxin (CDT) positivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 8 publications
3
39
2
2
Order By: Relevance
“…[3][4][5][6][7][8][9] The incidence of Clostridium difficile-associated diarrhea (CDAD) in patients undergoing APBSCT has been reported to be in the range of 5-7%. 1,2,6 A preliminary analysis from our group suggested that patients with multiple myeloma had a higher incidence of CDAD than reported previously. 7 The purpose of this study was to determine the incidence of CDAD in a larger cohort of patients who underwent APBSCT for multiple myeloma and to compare the incidence of CDAD in patients transplanted for multiple myeloma to patients transplanted for lymphoma.…”
Section: Introductionmentioning
confidence: 37%
See 3 more Smart Citations
“…[3][4][5][6][7][8][9] The incidence of Clostridium difficile-associated diarrhea (CDAD) in patients undergoing APBSCT has been reported to be in the range of 5-7%. 1,2,6 A preliminary analysis from our group suggested that patients with multiple myeloma had a higher incidence of CDAD than reported previously. 7 The purpose of this study was to determine the incidence of CDAD in a larger cohort of patients who underwent APBSCT for multiple myeloma and to compare the incidence of CDAD in patients transplanted for multiple myeloma to patients transplanted for lymphoma.…”
Section: Introductionmentioning
confidence: 37%
“…11,12 Second, our study only included patients with lymphoma and multiple myeloma in contrast to the other two studies, which included patients with other diagnoses. 2,6 More than half of the patients in the study by Bilgrami et al 6 had solid tumors, while the study by Tomblyn et al 2 included patients with other hematologic malignancies. As discussed below, it is not clear if the underlying diagnosis can predispose patients to CDAD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Reports show a 76-91 % incidence of diarrhoea in HSCT recipients (Tomblyn et al, 2002), and the incidence of CDI in these patients can be as high as 20 % (Bobak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%